Analysis of Aroma Quality of Pearl Orchid at Different Flowering Stages and Its Scented Tea - HUANG Cuixin, KUN Jirui, LIN Yunzhi, DAI Hongwei, WENG Tianjun, LI Zhengwen, TONG Huarong (Shipin Kexue)
In this study, sensory evaluation, headspace-solid phase microextraction-gas chromatography-mass spectrometry (HS-SPME-GC-MS) and odor activity value (OAV) were used to evaluate the aroma quality of pearl orchid flowers in five developmental stages: bud, initial bloom, semi-bloom, full bloom, and withering. Subsequently, principal component analysis (PCA), orthogonal partial least squares-discriminant analysis (OPLS-DA) and permutation tests were performed. The results showed that there were differences in the sensory evaluation and the types and contents of volatile compounds among pearl orchid flowers at different developmental stages. The fully blooming flower had the best aroma quality, being pure and long-lasting, followed by the semi-blooming and initially blooming flowers, which had a faint flowery aroma. The withering flowers had a flowery aroma with spoilage odor and the buds had no flowery aroma, but instead had a green odor, so neither of them could be used to scent tea. A total of 98 volatile compounds were detected at levels in the range of 77.521-200.838 μg/g, including 22 alcohols, 13 aldehydes, 36 olefins, 14 esters, 4 ketones and 9 others. The content of volatile compounds in the fully blooming flowers was the highest, including 28 aroma compounds with OAV > 1 and 9 substances with OAV > 50. Due to its good appearance, aroma characteristics and aroma release capacity, the fully blooming flowers were used to scent green tea and black tea. It was found that the contents of aroma components such as methyl jasmonate of pearl orchid flowers in the scented tea were obviously increased compared with those in the plain tea, indicating improved aroma quality of tea. To sum up, the fully blooming flowers of pearl orchid is the most suitable for making scented tea.